Analisis Kepatuhan Higiene Penjamah Makanan dan Sanitasi Peralatan di Whitespoon Catering Malang - Firjatulloh, Muhammad Bachtiar; Kholidah, Diniyah (Politeknik Kesehatan Kemenkes Malang, 2024)
Background: Food handler compliance with Standard Operating Procedures (SOP) for hygiene and the condition of kitchen equipment sanitation plays a crucial role in ensuring food safety. However, adherence to SOPs often becomes a challenge, especially in the catering sector. Objective: This study aimed to analize food handler compliance and kitchen equipment sanitation at Whitespoon Catering based on regulatory standards. Design: The study used a cross-sectional descriptive design and implementation evaluation, with data collection methods including observations, structured interviews, and questionnaires. Results: The findings showed that most food handlers’ compliance levels were in the